2009
DOI: 10.1007/s12522-009-0034-9
|View full text |Cite
|
Sign up to set email alerts
|

Screening, epidemiology, molecular biology, and treatment strategies for endometriosis‐associated ovarian cancer

Abstract: Ovarian endometrioma could be viewed as a neoplastic process, particularly in perimenopausal women. Understanding the mechanisms of endometriosis development and elucidating its pathogenesis and pathophysiology are intrinsic to prevention and the search for effective therapies of endometriosis-associated EOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…Malignant transformation is a rare complication of endometriosis, affecting 0.6-0.8% of all cases of OE (1). In Japan, clear cell carcinoma is not uncommon and is the second most frequently occurring type of EAOC, accounting for >20% of all EAOC cases (8). In the present case report, transvaginal ultrasonographic findings revealed a large pelvic mass and solid echogenic loculi.…”
Section: Discussionsupporting
confidence: 46%
“…Malignant transformation is a rare complication of endometriosis, affecting 0.6-0.8% of all cases of OE (1). In Japan, clear cell carcinoma is not uncommon and is the second most frequently occurring type of EAOC, accounting for >20% of all EAOC cases (8). In the present case report, transvaginal ultrasonographic findings revealed a large pelvic mass and solid echogenic loculi.…”
Section: Discussionsupporting
confidence: 46%
“…Seven reviews were found in the literature [4, 712], which have addressed the association between endometriosis and ovarian cancer. A summarizing table of the reviews' findings was modified from the Glasgow appraisal tool (Table 1) [6].…”
Section: Resultsmentioning
confidence: 99%
“…Endometriosis is associated with an increased risk of epithelial ovarian cancer development, especially clear cell and endometrioid carcinoma. Although clear cell and endometrioid subtypes are rare among all epithelial ovarian cancers, they are most common in endometriosis-associated ovarian cancer (EAOC) [ 8 , 9 , 16 ]. In our study, clear cell and endometrioid subtypes were found in 8 of 9 patients with invasive carcinoma.…”
Section: Discussionmentioning
confidence: 99%